Similarity Amidst Diversity: Lessons about Women Representation from Pati and Demak - Tawakkal, George Towar Ikbal; Utaminingsih, Alifiulahtin; Garner, Andrew D.; Wike, Wike; Seitz, Thomas R.; Putra, Fadillah (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
While the focus of most research in women's politics has been on the number of legislative seats and explaining the under-representation of women and other marginalized groups, we argue that there also needs to be a greater focus on voters themselves and their attitudes about gender representation in Indonesia. We focus on three broad series of questions. First, gender differences in attitudes about women candidates precisely. Second, gender differences in policy priorities. Third, gender differences in attitudes about one specific aspect of Indonesian elections – money politics or what is sometimes referred to as "vote-buying." The data are drawn from a stratified probability sample of citizens in the Demak and Pati regencies in Central Java, Indonesia. A total of 800 respondents were in the sample, including 55 percent of the sample consisted of women. The finding has some interesting implications in how to understand gender differences in Indonesian politics. Men and women both respond with the correct "rhetoric" view about the importance of women candidates and descriptive representation. Still, both genders shift from the "rhetoric" view to the "logic" view about policies that have a more direct impact on their own lives.